Herniarin Alleviates Lipopolysaccharide-Induced Acute Lung Injury in Mice via Regulating Oxidative Stress, Inflammation and Apoptosis Mechanisms - Jiang, Li; Zhang, Tao; Yan, Fangtao; Shen, Jian; Alarfaj, Abdullah A.; Hirad, Abdurahman Hajinur (Indian Journal of Pharmaceutical Education and Research, 2025)
Background: Acute Lung Injury (ALI) is a severe, serious condition characterized by the development of pulmonary edema, hypoxemia and respiratory distress. Objectives: The current work was intended to disclosing the beneficial activities of the herniarin against LPS-induced ALI in murine model. Materials and Methods: The mice were exposed to LPS for 3 days via the intra-tracheal route to trigger the ALI response. Oral administration of herniarin was given for 3 days to the mice subsequent to the LPS challenge. The mice underwent scarification under anaesthesia, subsequently lungs were excised and weighed accurately. The commercially procured assay kits were utilized to estimate the biochemical factors related to the apoptosis, inflammation and oxidative stress. The histopathological analysis was conducted on the lung tissues of the experimental mice. Results: In the present study, the treatment with the herniarin successfully reduced pulmonary edema, total protein and LDH activity in the mice with ALI. The MDA level was decreased, while the antioxidants GSH and SOD concentrations were elevated by the herniarin treatment. The herniarin treatment significantly decreased the inflammatory factor levels and inflammatory cell counts in the ALI mice. In addition, the herniarin treatment effectively decreased the Bax and caspase-3 expressions, whereas the Bcl-2 expression was increased in the ALI mice. Furthermore, the outcomes of histological investigation confirmed the therapeutic efficacy of herniarin against ALI. Conclusion: The present study revealed that herniarin successfully inhibited LPS-induced ALI in mice via inhibiting lung edema, inflammation, oxidative stress, apoptosis and lung damage. Hence, it can be concluded that herniarin has the potential for the management of ALI.
Keywords: Apoptosis; Herniarin; Inflammation; Lung edema; Malondialdehyde; Pulmonary